2003
DOI: 10.1128/aem.69.12.7091-7100.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification and Nitrifying Bacteria in the LowerSeine River and Estuary(France)

Abstract: The Achères wastewater treatment plant, located just downstream of Paris, discharges its effluents into the lower Seine River. The effluents contain large numbers of heterotrophic bacteria, organic matter, and ammonium and are a source of nitrifying bacteria. As a result, degradation of organic matter by heterotrophic bacteria and subsequent oxygen depletion occur immediately downstream of the effluent outlet, whereas nitrifying bacteria apparently need to build up a significant biomass before ammonium oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
112
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 57 publications
18
112
1
1
Order By: Relevance
“…Earlier studies have suggested that nitrite (Sahan and Muyzer, 2008) and pH (Nicol et al, 2008) may be determining factors in the niche differentiation between AOA and AOB, whereas salinity and hydrological factors have been suggested to have an influence on the structure and dominance of AOA or AOB communities (Stehr et al, 1995;Cebron et al, 2003;Francis et al, 2003;Bernhard et al, 2005;Dang et al, 2008;Mosier and Francis, 2008). This suggests that there are likely to be a number of potentially confounding environmental factors shaping ammonia oxidising communities in estuarine sediments.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies have suggested that nitrite (Sahan and Muyzer, 2008) and pH (Nicol et al, 2008) may be determining factors in the niche differentiation between AOA and AOB, whereas salinity and hydrological factors have been suggested to have an influence on the structure and dominance of AOA or AOB communities (Stehr et al, 1995;Cebron et al, 2003;Francis et al, 2003;Bernhard et al, 2005;Dang et al, 2008;Mosier and Francis, 2008). This suggests that there are likely to be a number of potentially confounding environmental factors shaping ammonia oxidising communities in estuarine sediments.…”
Section: Discussionmentioning
confidence: 96%
“…Reaction mixtures were incubated for 24 h in 100 ml polyethylene bottles in the dark at 20°C (Cébron et al 2003) with 50% (v/v) air headspace (de Bie et al 2002) and addition of NH 4 + (final concentration 2 mM) or NO 2 − (final concentration 0.36 mM).…”
Section: Measurement Of Potential and Actual Rates Of Ammonia And No mentioning
confidence: 99%
“…Secondly, NO 2 − was further oxidized to NO 3 − by nitrite-oxidizing bacteria (NOB) . AOA and nitrifying bacteria, including AOB and NOB, have been found in a variety of environments, such as various soils (Leininger et al 2006;Bartosch et al 2002;He et al 2007), rhizosphere (Herrmann et al 2008;Marilley and Aragno 1999), ocean water and sediments (Dang et al 2008;Kim et al 2006;Ward and Carlucci 1985), wastewater treatment plant bioreactors (Park et al 2006;Daims et al 2001;Siripong and Rittmann 2007), and freshwater ecosystems (Hatzenpichler et al 2008;Herrmann et al 2009;Cébron et al 2003;Cébron and Garnier 2005). Instead of being effectively eliminated, ammonia may accumulate in water columns especially in eutrophic lakes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depuis les années 1990, plusieurs travaux ont montré que l'azote ammoniacal (entre 1 et 4 mg N/L) apporté par les effluents de la station d'épuration Seine Aval (Achères, ouest de Paris), est complètement nitrifié au niveau de l'estuaire fluvial lors d'un transit de 200 km en aval, diminuant relativement peu sur le cours de la basse Seine (BRION et al, 2000;CÉBRON et al, 2003;GARNIER et al, 2001GARNIER et al, , 2006. L'activité nitrifiante maximale dans l'estuaire entraîne une désoxygénation importante.…”
Section: Introductionunclassified